2010
DOI: 10.1017/s0022112009993302
|View full text |Cite
|
Sign up to set email alerts
|

Roll convection of binary fluid mixtures in porous media

Abstract: We investigate theoretically the nonlinear state of ideal straight rolls in the RayleighBénard system of a fluid layer heated from below with a porous medium using a Galerkin method. Applying the Oberbeck-Boussinesq approximation, binary mixtures with positive separation ratio are studied and compared to one-component fluids. Our results for the structural properties of roll convection resemble qualitatively the situation in the Rayleigh-Bénard system without porous medium except for the fact that the streamli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Finally, with the boundary conditions (1.5) the equations are also equivariant with respect to the midplane reflection z → 1 − z. The latter symmetry favours roll-like patterns (Golubitsky, Swift & Knobloch 1984;Umla et al 2010) and therefore plays an essential role in the observed patterns.…”
Section: )mentioning
confidence: 99%
“…Finally, with the boundary conditions (1.5) the equations are also equivariant with respect to the midplane reflection z → 1 − z. The latter symmetry favours roll-like patterns (Golubitsky, Swift & Knobloch 1984;Umla et al 2010) and therefore plays an essential role in the observed patterns.…”
Section: )mentioning
confidence: 99%
“…For more details see Ref. [6]. We consider two infinite horizontal parallel plates perpendicular to a homogeneous gravitational field in z direction.…”
Section: A System and Basic Equationsmentioning
confidence: 99%
“…One can choose ≡ 0 and neglect Eq. (2.8a) as long as no transient behavior is investigated and there is no mean flow in the system [6]. The boundary condition on u implies = 0 at z = ± 1 2 .…”
Section: A System and Basic Equationsmentioning
confidence: 99%
See 2 more Smart Citations